Multi-modal phones revitalize markets in Senegal - Annerose, Daniel (Technical Centre for Agricultural and Rural Cooperation, 2002)
For almost a year now, Senegalese fruit and vegetable producers have been part of a revolution that has been brought about by Manobi, a mobile services operator and Internet specialist for the rural and agro-indus